Analisis Pengaruh Digital Marketing terhadap Pertumbuhan Penjualan UMKM Tinjauan Menggunakan Metode Systematic Literature Review: Analysis of the Influence of Digital Marketing on MSME Sales Growth Review Using the Systematic Literature Review Method - Tesa Vausia Sandiva; Jhon Veri (Program Studi Ekonomi Syariah, 2024)
This study uses the Systematic Literature Review (SLR) method to analyze the influence of digital marketing on sales growth of Micro, Small and Medium Enterprises (MSMEs). From a review of 19 articles published between 2019 and 2024, this research consistently shows that digital marketing strategies, such as the use of social media platforms and other digital marketing techniques, play an important role in increasing brand awareness, consumer engagement and sales conversions for MSMEs. Optimization Information technology infrastructure has also been proven to increase the effectiveness of digital marketing strategies in MSMEs. These findings have a significant impact on industry players and MSME related parties, emphasizing the importance of implementing and managing digital marketing strategies for sustainable business growth and competitive advantage in the current digital era. Keywords: Digital Marketing, UMKM, Systematic Literature Review (SLR)